INVESTIGATION OF LIQUID-PHASE OXIDATION OF NAPHTHENE-PARAFFINIC HYDROCARBONS OF BALAKHANY OIL (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Liquid-phase aerobic oxidation of naphthene-paraffinic hydrocarbons at 217-330о С of diesel fraction of Balakhany oils in the presence of the mixtures of Mn, Cr salts of natural petroleum acids (MeNPA) has been investigated. The catalytic oxidation process is realized for 7 hours at temperature 135-1400C in a barbotage reactor. Samples were taken every hour and oxidized product was separated by composition in accordance with known methods. Mechanism of oxidation process of naphthene-paraffinic hydrocarbons has been studied by IR- spectroscopy. It has been found that, after 5 hours oxidation of naphthene-paraffinic hydrocarbons the yield of obtaining synthetic petroleum acids rich 16,5%, the yield of oxysynthetic petroleum acids-18%. The changes of the optical density of a carbonyl and a hydroxyl groups depending on the time were studied. It was found that the oxidation reaction should be conducted within 6 hours, as D1713(C=O) and D941(OH) after 6 hours decrease and it’s probably connected with beginning decomposition process of the acids and oxyacids.